Implementation of the Reading Write Literacy Program to Elementary School Students About the Impact of the Natural Disaster of Mount Merapi - M. Indira Agustin; M. Muktiarni; Jonah Mupita (Universitas Pendidikan Indonesia, 2022)
The implementation of reading and writing literacy programs for elementary school students is needed because in the modern era there is a lack of interest in reading and writing owned by elementary school students. The purpose of this research is to implement literacy regarding the mitigation of the natural disaster of Mount Merapi for elementary school students. Because there are still many elementary school students who do not know the mitigation of the natural disaster of Mount Merapi. The method used in this study is a qualitative descriptive method in the form of an instrument used in distributing pre-test and post-test questionnaires. Contains 10 questions regarding the literacy program on the impact of the volcanic natural disaster, which is directed to elementary school. This is evidenced through a pre-test questionnaire at the beginning and the average result of 10 students before being given material on natural disaster mitigation is 45%. After students were given material through online learning media, the average results obtained increased by 80%. It is proven that based on the data obtained, most of the students have good knowledge about natural disaster mitigation. The impact felt by students related to the literacy program regarding the natural disaster of Mount Merapi, students are more concerned about natural disaster preparedness.